MAKNA DAN FUNGSI MAGIS SYAIR ACAPELLA PADA RITUAL PEMANDIAN SENJATA TRADISIONAL MASYARAKAT KEC. KEDUNGDUNG SAMPANG MADURA - Agustiningsih, Ika (Universitas Papua, 2018)
Research on the meaning and function of magical ritual bathing of traditional weapon of society Kec. Kedungdungheld every date one suro. Traditional weapon bathing rituals are held to commemorate the dhisah or so-called villagerituals. Society veil believe that by reciting acapella poem will add sanctity to the ceremony. this study aims to preservethe culture of Madurese society by seeking meaning and magical function against acapella poetry. This research alsouses hermenotika method that is searching for optimal meaning in acapella poetry and using descriptive qualitativeresearch type and using literary anthropology approach. Sources of data used are acapella and informant poems and usingdocumentation, recording, observation, recording, and interview techniques. Checking the validity of data in research istriangulation theory theory and methods obtained from books and journals.